A power compensator - Chaudhuri,B; Hui,SYR; Chaudhuri,NR; Lee,CK (2014)
A power compensator for compensating voltage at a location along a power transmission line, the compensator having a controller for controlling a voltage generated across the compensator, wherein the voltage is controlled to maintain a power transmission line voltage at a value dependent on the power transmission line location.